2021
DOI: 10.1371/journal.pone.0254437
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of seedling tolerance to exposure to low temperature in the maize IBM RIL population

Abstract: Maize is a cold sensitive crop that exhibits severe retardation of growth and development when exposed to cold spells during and right after germination, including the slowdown in development of new leaves and in formation of the photosynthetic apparatus. Improving cold tolerance in maize would allow early sowing to improve crop yield by prolonging a growing season and by decreasing the negative effects of summer drought, diseases, and pests. Two maize inbreds widely incorporated into American maize germplasm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Low-temperature stress can seriously affect normal crop development, and quinoa shows different levels of sensitivity to low temperatures at different stages of reproduction. Low-temperature stress at the seedling stage generally results in weak seedlings, delaying reproduction [ 30 ], and in severe cases, it causes extensive seedling mortality, ultimately affecting quality and yield.…”
Section: Discussionmentioning
confidence: 99%
“…Low-temperature stress can seriously affect normal crop development, and quinoa shows different levels of sensitivity to low temperatures at different stages of reproduction. Low-temperature stress at the seedling stage generally results in weak seedlings, delaying reproduction [ 30 ], and in severe cases, it causes extensive seedling mortality, ultimately affecting quality and yield.…”
Section: Discussionmentioning
confidence: 99%
“…Explorations of cold response at genotypic/species levels can further unveil the overall tolerance mechanism. For example, in maize [ 99 ], two widely used inbreds, i.e., B73 and Mo17 and 37 other inbreeds (grouped into stiff-stalk, non-stiff stalk and tropical clades) exhibited variable cold tolerance behaviour that was evaluated at seedling stages. Recombinant inbreed (B73 × Mo17) line (RIL) populations were developed (total of 97 RILs) to identify the QTLs responsible for the cold response at seedling stages.…”
Section: Membrane Transporters and Abiotic Stressesmentioning
confidence: 99%
“…Zhao et al [ 48 ] reported that the broad sense heritability ( ) of Pn, Tr, Rubisco activity, and WUE were 88.9%, 69.7%, 68.8%, 86.8% in a maize F 4 population of 218 lines under well-watered and water-stress environments, respectively, while their genotype × environment interaction heritability ( ) was 9.9%, 15.6%, 9.7%, and 1.5%, respectively. Goering et al [ 49 ] showed that the of chlorophyll concentration, i.e., absorbance at 663 nm (Chl a) and 645 nm (Chl b) were 88.5% and 82.5% in a maize IBM recombinant Inbred Lines (RIL) population at 24 °C and 4 °C conditions, respectively. David et al [ 50 ] analyzed the genetic basis of SOD activity, CAT activity, POD activity, APX activity, root length, and root weight by QTL mapping in rice.…”
Section: Discussionmentioning
confidence: 99%